Slouching Towards Monell: The Disappearance of Vicarious Liability Under Section 10(B) - Ann M. Lipton (Washington University Law Review, 2015)
Liability under section 10(b) of the Securities Exchange Act is one of the primary mechanisms for enforcing the federal securities laws. Section 10(b), however, prohibits only intentional or reckless deception, and there has never been consensus as to how to determine whether an organization, rather than a natural person, harbors the relevant mens rea. Traditionally, organizational liability under federal law is determined according to agency principles, and most courts pay lip service to the notion that agency principles govern under section 10(b). As this Article demonstrates, they do not. Many section 10(b) actions involve “open-market” frauds, whereby the allegedly fraudulent statements are issued publicly under the corporate imprimatur. These statements depend on agents operating at all levels of the company, who may intentionally or recklessly pass along inaccurate information through corporate reporting channels. In such circumstances, the actus reus that forms the basis of the section 10(b) violation—the false public statement—has been disaggregated from the actor who harbors mens rea. As this Article shows, courts have used this disaggregation to eschew the agency principles applied in other areas of law. Courts instead seek to impose a form of “direct” organizational liability tied to the actions and omissions of the organization’s highest-level authorities. This regime is, in practical effect, strikingly similar to the regime used to determine the liability of local governments under § 1983, where vicarious liability has been formally rejected by the Supreme Court. Though these two statutes would seem to have little in common, this Article argues that vicarious liability has been rejected under both regimes for similar policy reasons. Among other things, as federal corporate disclosure requirements—backed by the threat of section 10(b) liability—expand into a mechanism for substantively regulating the quality of corporate governance (a matter traditionally left to state law), courts have pushed back by limiting vicarious liability in order to distinguish “true” fraud claims from garden-variety mismanagement. Similarly, in the § 1983 context, the elimination of vicarious municipal liability functions, as a practical matter, to distinguish matters of federal constitutional concern from ordinary state law torts. This Article ultimately concludes that, despite the criticisms that have been leveled at the current approaches to organizational liability under § 1983, § 1983 doctrine may in fact improve jurisprudence under section 10(b). Courts considering section 10(b) claims may borrow from jurisprudence developed under § 1983 to formulate objective standards of fault, in order to prevent high-level corporate authorities from insulating themselves from knowledge of wrongdoing at lower levels of the corporate hierarchy.
Keywords: Securities Exchange Act; Securities Law; Vicarious liability; Monell; Intentional or reckless deception; Organizational liability; Section 10(b); Section 10b